UPAYA PENINGKATAN KUALITAS MANAJEMEN HIDUP DAN PENCEGAHAN PENYAKIT DEGENERATIF DI SEKOLAH LANSIA MELATI - Hasrijal, Hasrijal; Sonang Siregar, Pariang; Suhermon, Suhermon; Herty, Tety; Amin Mulya, Riski (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
The Melati Elderly School in Koto Tinggi Village was established as a form of non-formal education aimed at improving the quality of life of the elderly through the seven dimensions of resilient aging, which include spiritual, physical, emotional, intellectual, social, vocational, and environmental aspects. This Community Service Program (PKM) seeks to promote healthy lifestyle management and prevent degenerative diseases among elderly students. The implementation methods included the development of the “Elderly Fitness Information System” website as a health monitoring tool, health awareness campaigns, elderly exercise sessions, as well as health check-ups and consultations. The program involved 27 elderly students with the support of medical staff and educators. The results demonstrated an increase in elderly participants’ knowledge about healthy living, greater involvement in physical exercise, and the availability of a simple technology-based tool for continuous health monitoring. This initiative has contributed to the realization of elderly individuals who are healthy, independent, active, productive, and dignified. Therefore, this PKM program is considered effective in enhancing quality of life while preventing degenerative diseases among the elderly.